IN VITRO PROPAGATION IN CLINACANTHUS SIAMENSIS BREMEKA MEDICINAL TAXON OF WESTERN GHATS, INDIA - BEENA PRABHA; N. SAVITHRAMMA (International Journal of Pharma and Bio Sciences, 2015)
In vitro propagation through nodal explants by indirect organogenesis of Clinacanthus siamensis Bremek. Nodal segments were surface sterilised in NaOCl for 5 min. This is followed by treating it with 0.1% Hgcl2 for 8 min. Different concentrations of BAP and 2- P were added to full strength MS medium for culture initiation. Multiple shoots were formed in MS medium augmented with various concentrations of BAP and a maximum number of 5.8 ± 0.37 after 30 days with a mean length of 7.38 ± 0.17 cm. In vitro derived shoot segments approximately of 1.0 cm length were dissected and cultured in full strength MS medium augmented with various concentrations of 2,4- D and 2,4,5- T. Observations were made after 4 weeks of culture and found that three types of calli were formed. Further, shoot regeneration is induced from 500 mg fresh weight of friable callus in MS medium with different concentrations and combinations of 2,4-D and BAP, which induced maximum shoot multiplication followed by elongation after 4weeks of culture. Rooting was maximum with combinations of 2,4-D and IBA and IBA alone. These in vitro regenerated plants were successfully acclimatized and transferred to green house. Hardened plants were transplanted into sand and soil (1:1).